2010
DOI: 10.1007/s00441-010-0949-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of α7 nicotinic acetylcholine receptors in human periodontal ligament fibroblasts and rat periodontal tissues

Abstract: Tobacco smoking is the main risk factor associated with chronic periodontitis, but the mechanisms that underlie this relationship are largely unknown. Recent reports proposed that nicotine plays an important role in tobacco-related morbidity by acting through the nicotinic acetylcholine receptors (nAChRs) expressed by non-neuronal cells. The aim of this study was to investigate whether alpha 7 nAChR was expressed in periodontal tissues and whether it functions by regulating IL-1 beta in the process of periodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 29 publications
7
37
0
3
Order By: Relevance
“…In previous studies, we demonstrated the functional expression of α7 nAChR in human and rat periodontal tissue. Up-regulation of α7 nAChR upon the administration of nicotine could be inhibited by pretreatment with α-BTX, the α7 nAChR antagonist [9], suggesting that nicotine could affect smoking-associated periodontitis via α7 nAChR.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated the functional expression of α7 nAChR in human and rat periodontal tissue. Up-regulation of α7 nAChR upon the administration of nicotine could be inhibited by pretreatment with α-BTX, the α7 nAChR antagonist [9], suggesting that nicotine could affect smoking-associated periodontitis via α7 nAChR.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine is a lipophilic molecule of which the effects on neuronal nicotinic acetylcholine receptors (nAChR) have been primarily focused on its physiologic impact within the confines of the nervous system (Mao et al, 2011). However, many studies have recently found neuronal nAChRs to be expressed on many different non-neuronal cell types throughout the body (Chernyavsky et al, 2005;Resende et al, 2008;Wang et al, 2010;Wessler and Kirkpatrick, 2008). Recently, studies have found that nAChRs can be expressed on oral gingival and periodontal tissues (Nguyen et al, 2000;Wang et al, 2010).…”
Section: Discusstionmentioning
confidence: 99%
“…However, many studies have recently found neuronal nAChRs to be expressed on many different non-neuronal cell types throughout the body (Chernyavsky et al, 2005;Resende et al, 2008;Wang et al, 2010;Wessler and Kirkpatrick, 2008). Recently, studies have found that nAChRs can be expressed on oral gingival and periodontal tissues (Nguyen et al, 2000;Wang et al, 2010). The expression of α7 nAChR in periodontal tissues can initiate the function of the regulation IL-1β in the process of periodontitis (Wang et al, 2010).…”
Section: Discusstionmentioning
confidence: 99%
See 2 more Smart Citations